UPAYA PENINGKATAN HASIL BELAJAR BAHASA INGGRIS MATERI DESCRIPTIVE TEXT DAN PARTISIPASI PESERTA DIDIK MELALUI PRAKTIK PEMBELAJARAN BERDIFERENSIASI - Silvana, Rini (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2024)
Abstract This research aims to describe how differentiated learning helps improve learning outcomes and learners’ participation during learning and how learners perceive learning experiences that accommodates their varied learning needs. To achieve this goal, classroom action research was carried out with a process of planning, implementing, developing and reflecting in grade X (ten) IPS 2 MAN 1 Tangerang Municipality. Differentiated learning is applied during the process of learning descriptive texts with local wisdom context. This research used teacher’s journal, tests, and interviews to obtain data. The data was then analyzed descriptively and comparatively to determine the progress of students in learning descriptive texts from cycle 1 to cycle 2. Teacher journals and interviews helped record learners’ participation during the process and understand their attitudes towards the implementation of differentiated instruction. The results of the study indicate that differentiated learning helps improve student learning outcomes where, before the intervention, the average score achieved by students was 72.5 with a percentage of 47.5% in the insufficient criteria. This increased to 77.5 with a percentage of 67.5% in the sufficient category in cycle 1. The average student score in cycle 2 was 83.27 with a percentage of 86% in the very good criteria.  Observations recorded in the teacher's journal confirmed the increase in learners’ participation as seen in their readiness and preparation, participation in discussion as well as response to questions. The interview results reinforced the positive attitude of students towards the experience of learning descriptive texts with differentiated instruction practices.  Abstrak Penelitian ini bertujuan untuk menggambarkanbagaimana pembelajaran berdiferensiasi membantu meningkatkan hasil belajar dan partisipasi peserta didik serta bagaimana sikap peserta didik terhadap pengalaman belajar yang mengakomodasi kebutuhan belajar peserta didik yang bervariasi. Untuk mencapai tujuan tersebut, penelitian tindakan kelas dilaksanakan dengan proses perencanaan, pelaksanaan, pengembangan dan refleksi di kelas X (sepuluh) IPS 2 MAN 1 Kota Tangerang. Pembelajaran berdiferensiasi ini diterapkan selama proses pembelajaran teks Deskriptif dengan konteks kearifan lokal. Penelitian ini menggunakan jurnal guru, tes, dan wawancara untuk memperoleh data. Data kemudian dianalisis secara deskriptif komparatif, untuk mengetahui kemajuan peserta didik dalam mempelajari teks deskriptif dari siklus 1 ke siklus 2. Jurnal guru dan wawancara membantu mencatat partisipasi peserta didik selama proses dan mengetahui sikap peserta didik terhadap pelaksanaan pembelajaran berdiferensiasi. Hasil penelitian mengindikasikan pembelajaran berdiferensiasi membantu meningkatkan hasil belajar peserta didik dimana sebelum tindakan nilai rata rata yang dicapai peserta didik adalah 72,5 dengan prosentase 47,5% kriteria kurang, meningkat menjadi 77, 5 dengan prosentase 67,5% kategori cukup di siklus 1.  drata rata peserta didik pada siklus 2 adalah 83,27 dengan prosentase 86 % kriteria baik sekali.  Hasil pengamatan yang dicatat dalam jurnal guru selama tindakan mengkonfirmasi peningkatan partisipasi aktif peserta didik dilihat dari kesiapan dan persiapan, keaktifani dalam diskusi dan respon terhadap pertanyaan. Hasil waancara menguatkan sikap positif peserta didik terhadap pengalaman belajar teks deskriptif dengan praktik pembelajaran berdiferensiensi. Penelitian ini merekomendasikan implementasi pembelajaran berdiferensiasi untuk meningkatakan hasil belajar dan partisipasi peserta didik bahasa inggris materi teks deskriptif.